P2_7 Mobile Suit Gundam: Falling From Space - Hall, Rosanna; West, Andrew; McHugh, Melissa; Blake, James (Physics Special Topics, 2011)
Â In order for a Mobile Suit to be unable to escape the Earth’s gravity at an altitude of 100km with 40% of the propellant fuel available it would have to be travelling towards the Earth at 27,431ms-1. The increase in temperature due to the resistive drag forces felt upon re-entry would require an active cooling system with an output of 112MW which is over 37 times greater than known power outputs on board Mobile Suits.